Changes in some biophysical characteristics of African horsesickness virus (no. 3922) during attenuation - Russell, B.W (Animal Demography Unit (ADU), 2020)
African horsesickness virus (No.3922, Type 7), attenuated for the horse by serial passage in suckling mouse brain, was studied at various passage levels to determine whether any change in the biophysical characters of the infectious particles had occurred. during the process of attenuation. Such changes were indeed observed. Propagation of the virus in tissue culture was accomplished only after the modification of standard culture media by the addition of egg white, a complex substance containing a number of proteins including the enzyme lysozyme. Some evidence is presented to show that the presence of egg white materially assisted in the successful cultivation of horsesickness virus; as well as in the formation of plaques in monolayers ·of cultured cells. Electron micrographs of horsesickness virus obtained from these cultured cells, and the results of a study of the fine structure of infected mouse nervous tissue, are presented. A remarkable change in the buoyant density of the infectious particles of this horsesickness virus was found to occur during attenuation. The 'wild' or virulent strain was found to consist mainly of particles of density 1.26 gm/ml. The attenuated strain however proved to be composed of particles with deneities quite different from that of the wild strain, predominantly 1.21 and 1.34 gm/ml. This alteration of the buoyant appeared to be directly related to the degree of attenuation. Studies in electrophoresis using a newly designed apparatus showed that the wild strain of horsesickness virus is homogeneous in its migration in an electric field. The attenuated strain showed a changed electrophoretic pattern· indicating the presence of particles of different mobilities. As in density gradient analysis, electrophoresis showed a fundamental difference between the wild and attenuated strains of this virus. It was possible also to show a correlation between the slowly migrating component of the attenuated strain and the fraction of higher density. The sedimentation coefficient of the infectious particles of the No.3922 strain of horsesickness virus was studied at various stages of attenuation ·and the particle size at three passage levels were calculated. The particle size and other characteristics determined in this way were compared with the results of measurements obtained from ultrafiltration of the virus through collodion membranes. It was found that the diameter of the infectious particles of the attenuated strain is greater than that of the wild strain. This study shows that physical measurements may be used to give